Adherence: a review of education, research, practice and policy in Australia - Krass I; Aslani P (Pharmacy Practice, 2009)
Community pharmacists are well placed to deliver adherence support services as well as other pharmaceutical services to patients. They are often the last point of contact with patients collecting medicines in the healthcare chain, and they tend to be visited by patients on a regular basis to collect prescription medicines. They have the opportunity to reinforce information already received from other health practitioners, provide further information and monitor adherence to therapy.The past decade has seen an increase in focus on the importance of adherence to therapy, not only in the higher education sector, but also in government policy and community pharmacy practice. Adherence monitoring and promotion has not only become the foundation of courses taught in pharmacy schools, but has become an essential component of disease management and pharmaceutical services delivered by community pharmacists.Aims: This article aims to describe the education, research, practice and policy in the area of adherence to therapy in Australia with a focus on community pharmacists.Methods: A search of MEDLINE and International Pharmaceutical Abstracts as well as hand searches of the bibliographies of retrieved articles was conducted for the period 2000-2008. All pharmacy schools in Australia were also contacted to obtain information on the patient adherence to therapy content of their courses.Results: Ten studies met the inclusion criteria. Only one study had a specific adherence focus, with the remainder including adherence support and monitoring as part of the overall interventions delivered by the community pharmacists. In the majority of cases the interventions resulted in an improvement in patients’ adherence to therapy. The research was supported by government and pharmacy professional organisation initiatives in the area of cognitive pharmaceutical services. All universities which responded delivered specific patient adherence courses. Conclusions: Australian pharmacy schools are educating cohorts of students who will have the skills to monitor and support patient medication adherence in the context of contemporary pharmacy practice. This is supported by research evidence, government policy and fits well into the move to expand community pharmacy services to include chronic disease state management and primary health care.